Adaptive Neural Control for Gait Coordination of a Lower Limb Prosthesis. (1st February 2022) - Ma, Xin; Xu, Jian; Fang, Hongbin; Lv, Yang; Zhang, Xiaoxu
Highlights: Propose a new gait planning strategy to inherit intelligent human adaptability. Realize the environment adaptability and high GC performance simultaneously. Design a low-level neural control with cubic order evolution rule by Lyapunov's stability theory. Achieve application effectiveness for better control accuracy, faster convergence speed, and lower controlled torque. Abstract: Because of distinct differences in structure and drive, the lower limb amputee that walks with prosthesis forms a heterogeneous coupled dynamic system. The strongly coupled nonlinearity makes it difficult for the lower limb prosthesis (LLP) to adapt to complex tasks, such as variable-speed walking and obstacle crossing. As a result, the typical behavior can be seen as gait incoordination or even gait instability. This paper proposes a new gait-coordination-oriented adaptive neural sliding mode control (GC-ANSMC) for the heterogeneous coupled dynamic system. At the high level, the controller adopts the homotopy algorithm, which inherits the intelligence of the healthy lower limb (HLL), to create the GC-oriented desired trajectory for the LLP. The embedding parameter of the homotopy algorithm is updated online based on the mean difference between the lab-based target trajectory and the HLL's delayed motion, resulting in better GC performance. In addition, the new GC-planning strategy has sufficient environmental adaptability with a limited lab-based target trajectory for complex tasks. At the low level, radial basis function neural network (RBFNN) is employed to model the human-prosthesis heterogeneous coupled system uncertainties online and generate the controlled torques for simultaneous uncertainty compensation and gait driving. According to Lyapunov's theory, the sliding mode gains and the cubic order evolution rules of the network's weight are carried out. As a result, the global convergence of the proposed control approach can be ensured, and the dynamic motion could be quickly tracked. Applications for the variable-speed walking and the obstacle crossing show that the present GC-ANSMC could achieve better control accuracy, faster convergence speed, lower controlled torques, and higher GC performance than traditional methods. These advantages, as a result, indicate a convincing potential for the adaptive control for the nonlinear human-prosthesis heterogeneous coupled dynamics in complex tasks. Graphical abstract: Image, graphical abstract